2016
DOI: 10.1111/jce.13019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Left Atrial Voltage‐Based Catheter Ablation of Persistent Atrial Fibrillation

Abstract: Additional LVZ-based substrate modification after PVI improved the outcome in PeAF patients with LVZs, whereas PVI alone worked in patients without LVZs, even in those with PeAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(210 citation statements)
references
References 39 publications
8
195
5
2
Order By: Relevance
“…Bipolar electrograms were filtered by a bandpass to frequencies between 30 and 500 Hz. In accordance with the previous studies, an LVA was defined as an area with a bipolar peak‐to‐peak electrogram amplitude of < 0.5 mV and electrical scar areas as < 0.1 mV and covering > 5% of the LA body surface area. The LA surface area was defined as the LA body area without the PV antrum regions inside the PVI line.…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…Bipolar electrograms were filtered by a bandpass to frequencies between 30 and 500 Hz. In accordance with the previous studies, an LVA was defined as an area with a bipolar peak‐to‐peak electrogram amplitude of < 0.5 mV and electrical scar areas as < 0.1 mV and covering > 5% of the LA body surface area. The LA surface area was defined as the LA body area without the PV antrum regions inside the PVI line.…”
Section: Methodsmentioning
confidence: 86%
“…In this study, the extent of the LVZ was categorized on the basis of the LA fibrosis grade evaluated by delayed‐enhancement magnetic resonance imaging (MRI) . Various additional LVA‐based substrate modification procedures after the PVI have been reported in patients with nonparoxysmal AF having LVAs . In many patients with AF, individually located sites and/or patchy fibrotic areas targeted specifically for ablation have been found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Catheters with smaller electrodes and closer interelectrode spacing may be suitable to determine the area of low voltage more accurately. Yamaguchi et al demonstrated the usefulness of regional ablation of low-voltage areas (Figure 3), 39 while Kottkamp et al proposed circumferential isolation of lowvoltage areas, so-called box isolation of fibrotic areas (BIFA) (Figure 4). 36 BIFA would be suitable for patients with massive fibrosis in the LA, although its effect in such cases is reported to be limited.…”
Section: Endpoint Of Pvimentioning
confidence: 99%